PENGGUNAAN HYPOTHETICAL LEARNING TRAJECTORY (HLT) PADA MATERI ELASTISITAS UNTUK MENGETAHUI LINTASAN BELAJAR SISWA KELAS X DI SMA NEGERI 1 INDRALAYA UTARA - Putri Ramadhanti (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2015)
This study aims to a learning trajectory about elasticity for tenth grade students ofSMA Negeri 1 Indralaya Utara by using Hypothetical Learning Trajectory (HLT). The methodused in this study is design research. The subjects of this research were six students in the pilotexperiment and 24 students in the teaching experiment. A set of activities designed in HLT wasapplied and developed to gain the understanding of elasticity concept. The HLT designedduring the preparation phase was compared to the students’ actual learning trajectory duringthe implementation in the teaching experiment. Retrospective analysis of the teachingexperiment showed that students have diverse conjecture thinking in understanding the conceptof elasticity. This learning trajectory describes the development of student’s understanding inmaterial of elasticity during the learning process that consists of learning goals, learningactivities and conjecture of students’ thinking. Students who initially assumed that elasticmaterial only rubber and spring, after the observing and classifying objects of elastic and nonelasticactivities,startedtounderstandtheconceptofelasticityandtheelasticlimit.Inthenextactivity,choosing plastic experiment, students could determine the modulus of elasticity of anobject. Some students assumed that all spring have the same constants, after Hooke’s lawexperiment and created the graphs of Hooke’s law, student understood that the elasticity of thespring depends on the spring constant. It was got by students analyzing about the relationshipof force F with the length of the spring (extension   ). Based on this research, it was foundthat the use of HLT could determine the students' learning trajectory in understanding theconcept of elasticity.